Prevalence of Capnocytophaga canimorsus and Capnocytophaga cynodegmi in dogs and cats determined by using a newly established species-specific PCR - Suzuki, Michio; Kimura, Masanobu; Imaoka, Koichi; Yamada, Akio (Veterinary microbiology, 2010)
Capnocytophaga canimorsus and Capnocytophaga cynodegmi, fastidious gram-negative rods, are commensal microbes thriving in the oral cavities of dogs and cats. C. canimorsus can sometimes cause fatal systemic infections in humans. In the present study, we established a specific PCR which could identify and distinguish C. canimorsus from C. cynodegmi. The prevalence of Capnocytophaga spp. in dogs and cats was determined using this method. C. canimorsus was detected in 74% of dogs and 57% of cats. C. cynodegmi was detected in 86% of dogs and 84% of cats. The prevalence of Capnocytophaga spp. obtained in this study is somewhat higher than those reported previously where bacterial isolation method was used for identification. This is probably due to the fact that the PCR detection is more sensitive compared to bacterial isolation. Our findings suggest the importance of informing people who belong to high-risk groups as well as health care workers on C. canimorsus infection and its potential risk to people particularly to those who are immunocompromised.